Sildenafil is Safe and Effective for the Treatment of Lower Ureteric Stone with no Major Side Effect - KC, Sudeep Raj; Timilsina, Bhusan Raj; Upadhyay, Hari Prasad; Devkota, Gaurav; Shah, Rajiv; Lamichanne, Nirmal (Birat Journal of Health Sciences, 2019)
INTRODUCTION: Urolithiasis is one of the most common diseases of the urinary tract. Prevalence of urinary stones in a life time is approximately 1% to 15%.Peak age of incidence is 30 years. Male are more commonly affected than female about 2 to 3 times. At the time of presentation 20 % of the calculi are found in the ureter, among which 70% are located in the distal third of the ureter. OBJECTIVE: To study the effect of sildenafil citrate on passage of stone from distal ureter. METHODOLOGY: This is the Quasi experimental study performed in College Of Medical Sciences, Chitwan, Nepal, from February 2017 to February 2018 for a period of one year. First 100 patients of urolithiasis were selected and divided into two groups with the help of lotiery method Group A and Group B. In group A we had patient on placebo and in group B we had patient receiving sildenafil 50 mg once daily and for the period of two weeks. RESULTS: The mean ± standard deviation of stone size was 7.01±1.70mm for treatment group and 6.85±1.56mm for placebo group (p> 0.64) .The stone expulsion rate was 74.5% for treatment group and 41.7% for placebo group (P<0.001). Mean ± standard deviation of expulsion time was 7.6 ±3.49 days for treatment group and 10.25±3.12 days for placebo group (P<0.008). Mean ± standard deviation of VAS was 3.49±1.300for treatment group and 6.77±1.308 for placebo group (P<0.0001). CONCLUSION: Medical Expulsive Therapy (MET) for lower ureterolithiasis with sildenafil during conservative treatment period is safe and effective as demonstrated by the absence of serious side effects and increased stone expulsion rate with early time.